Kualitas Beton SCC dengan Substitusi Agregat Halus Tailing Tambang Emas Daerah Pongkor - Amalia, Amalia; Riyadi, Muhtarom (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
This paper presents the results of self compacting concrete (SCC) with water cement ratio 0.30 with four variations of tailings, ie 0%, 5%, 10% and 15%. Superplastisizer used is a type Naptha 511P of PT.Karya Naptha Belide. The results showed that (1) The use of tailings as fine aggregate in concrete SCC, has good workability. The fresh concrete that uses tailings, passing ability and filling ability is decrease. The use of tailings up to 15% of eligible properties filling ability and passing ability of SCC, (2) The more tailings used in SCC, setting time of concrete becomes longer, (3) Concrete with tailings as fine aggregate have unit weight is smaller than the concrete with fine aggregate sand, (4) Concrete with tailings has higher compressive strength and modulus of elasticity than concrete without tailings, (5)The use of tailings in concrete can lower tensile strength of concrete, (6)The optimum replacement of tailing found to be 10% in the concrete.